Dynamic Governance in an Effort to Reduce Unemployment Rate in Karawang Regency 2019-2023 - Raja Muhammad Azhari; Samugyo Ibnu Redjo; Neneng Yani Yuningsih (Journal of Law, Politic and Humanities, 2024)
This research is motivated by the problems occurring in Karawang Regency, namely the increasing unemployment rate due to the high Regency/City Minimum Wage (UMK), the shift in investment from labor-intensive to capital-intensive, the Covid-19 pandemic, inadequate labor absorption, and competition between indigenous communities. Karawang Regency and immigrants. Dynamic Governance of the Karawang Regency Government is something that can be seen to determine the ability of the Karawang Regency Government to deal with the dynamics that occur in the unemployment problem. The aim of this research is to determine the dynamic governance of the Karawang Regency Government in reducing unemployment in 2019-2023. In this research, the author used descriptive qualitative methods. Data collection was carried out by interviews, observation and documentation. Determination of informants was determined using purposive techniques. The research results show that the Karawang Regency Government's dynamic governance in reducing unemployment can be seen from three aspects of dynamic governance. These three aspects are culture with elements of markets, namely a fair market, long term, namely long-term plans, relevance, namely policies that are in accordance with wishes, growth, namely growth, and stability, namely stability. The second aspect of capabilities with a thinking ahead element is thinking ahead about problems that occur, thinking again, namely carrying out a review or rethinking existing policies and programs, and thinking across, namely thinking across boundaries by adopting various methods from existing references. Lastly, the change aspect is the result of the culture aspect and the capability aspect. In this case, the Karawang Regency Government has implemented dynamic governance by reducing the unemployment rate with various programs and policies in Karawang Regency, which in 2019-2022 experienced fluctuations. Based on the research results, it can be concluded that the Karawang Regency Government's handling of reducing unemployment has produced positive results. So that adaptive policies can be created. The researcher's suggestion is that the Karawang Regency Government can collaborate with the surrounding Regional Government to discuss the problem of unemployment so that relationships can be established and create programs that can be worked on together or new policies. The government must also know its duties as the executor of existing policies. Don't forget to maintain consistency in carrying out tasks, principals and functions.